Trends in maternal mortality at the University of Calabar Teaching Hospital, Nigeria, 1999–2009 - TU Agan; EI Archibong; JE Ekabua; et al (Dove Medical Press, 2010)
TU Agan1, EI Archibong1, JE Ekabua1, EI Ekanem1, S E Abeshi1, TA Edentekhe2, EE Bassey21Department of Obstetrics and Gynecology and 2Department of Anesthesia, College of Medical Sciences, University of Calabar Teaching Hospital, NigeriaBackground: Maternal mortality remains a major public health challenge, not only at the University of Calabar Teaching Hospital, but in the developing world in general.Objective: The objective of this study was to assess trends in maternal mortality in a tertiary health facility, the maternal mortality ratio, the impact of sociodemographic factors in the deaths, and common medical and social causes of these deaths at the hospital.Methodology: This was a retrospective review of obstetric service delivery records of all maternal deaths over an 11-year period (01 January 1999 to 31 December 2009). All pregnancy-related deaths of patients managed at the hospital were included in the study.Results: A total of 15,264 live births and 231 maternal deaths were recorded during the period under review, giving a maternal mortality ratio of 1513.4 per 100,000 live births. In the last two years, there was a downward trend in maternal deaths of about 69.0% from the 1999 value. Most (63.3%) of the deaths were in women aged 20–34 years, 33.33% had completed at least primary education, and about 55.41% were unemployed. Eight had tertiary education. Two-thirds of the women were married. Obstetric hemorrhage was the leading cause of death (32.23%), followed by hypertensive disorders of pregnancy. Type III delay accounted for 48.48% of the deaths, followed by Type I delay (35.5%). About 69.26% of these women had no antenatal care. The majority (61.04%) died within the first 48 hours of admission.Conclusion: Although there was a downward trend in maternal mortality over the study period, the extent of the reduction is deemed inadequate. The medical and social causes of maternal deaths identified in this study are preventable, especially Type III delay. Efforts must be put in place by government, hospital management, and society to reduce these figures further. Above all, there must be an attitudinal change towards obstetric emergencies by health care providers.Keywords: trends, maternal mortality, Nigeria